ANALYSIS AFFIXATION USAGE ON SONGS LYRICS OF HANDWRITEN ALBUM BY SHAWN MENDES - Ni Luh Ruska Antarika; Ni Putu Astiti Pratiwi (Jurnal Inovasi Penelitian, 2021)
The purpose of this research is to determine the affixation in The Script song lyrics. The primary goal of this research is to determine how the affixation process occurs in the lyric "Handwritten album By Shawn Mendes" from The Script. This research is a descriptive qualitative research, namely the research method used to collect, classify, and analyze the data which is then concluded from the analyzed data. The data was extracted from the lyric's text script. This analysis demonstrates that affixation occurs.